2012
DOI: 10.1093/jnci/djs176
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Cancer After False-Positive Test Results in Screening Mammography

Abstract: The implementation of new assessment technology coincided with a decrease in the size of excess risk of breast cancer for women with false-positive screening results. However, it may be beneficial to actively encourage women with false-positive tests to continue to attend regular screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…A study from the Copenhagen program in Denmark by von Euler‐Chelpin et al. found a 67% increased risk of breast cancer diagnosis in women with false‐positive results . Castells et al.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Copenhagen program in Denmark by von Euler‐Chelpin et al. found a 67% increased risk of breast cancer diagnosis in women with false‐positive results . Castells et al.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study from Denmark examined the long-term risk of breast cancer and found a 67% increased risk among women with a prior false-positive result (7). More recently, data from a population-based breast cancer screening program in Spain reported that false-positive results involving fine needle aspiration cytology or a biopsy had a higher subsequent cancer detection risk than those false-positive results involving additional imaging procedures alone (8).…”
Section: Discussionmentioning
confidence: 99%
“…The density coding was re-evaluated using data from a Copenhagen study on long-term breast cancer risk in women with false-positive screening test [21]. In total, 118 negative screening mammograms taken prior to the false-positive screening were re-evaluated.…”
Section: Methodsmentioning
confidence: 99%